Analisis pajak penerangan jalan dan pengaruhnya terhadap sektor listrik, gas, dan air di Kabupaten Tanjung Jabung Barat - Nur Hakiki; Chandra Mustika; Zamzami Zamzami (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2018)
The purpose of this study is to analyze the street lighting tax and its effect on the gas and water electricity sector in Tanjung Jabung Barat District. In addition, the authors identified the development and tax contribution of street lighting. Tanjung Jabung Barat Regency, the level of effectiveness of street lighting tax in tanjung jabung barat district and the influence of street lighting tax output on the electricity, gas and water sector in the West Tanjung Jabung Regency. This study used secondary data from the period 2006 to 2013. The data analysis method used in the study this is a descriptive quantitative method with regression analysis in interpolation data. In terms of its contribution to Regional Original Revenue